Extraction and Characterization of Antifungal Substances from Brevundimubsonas diminuta and Their Effect on Fusarium oxysporum - Shakir Alattar , Nagham; Burhan ALdeen, Sana; Al Shahwany, Ayyad Wajih (Iraqi Journal of Science, 2023)
Eighty one bacterial isolates were obtained from 53 soil samples of different plants rhizosphere. All the isolated bacterial were screened for antifungal effect against Fusarium oxysporum . Three isolates gave antifungal activity with inhibition zone ranged between (0.5-2.5 cm). Two isolates (Bd1 and Bd2) were Brevundimonas diminuta, while the third (Pf1) was Pseudomonas fluorescence . B. diminuta (Bd1) which used in this study isolated from Raphanus sativus gave the highest inhibition zone against F. oxysporum. Cell free supernatant of B.diminuta(Bd1) was better in antifungal activity than bacterial cells against F. oxysporum. The highest antifungal substance production was obtained from mineral salt broth containing 1% peptone after incubation at 350C for 7 days at pH=7. It was observed that no one of the three carbon sources (D- glucose , lactose and starch ) and lipid sources ( tween 80 , sun flower and olive oil) had an effect on antifungal substances production .Other factors were studied , B.diminuta (Bd1) produced protease, while did not produce chitinase and cellulase enzymes, also was unable to produce emulsifier substance but produced volatile compounds with antifungal activity against F. oxysporum. The results showed that chloroform at dilution 1:3 (v:v) was more efficient than methanol for antifungal substance extraction. The antifungal substances reduced the spores number of F. oxysporum using Malt Extract Agar after 7 days of incubation, while the bacterial cells reduced the spores number F. oxysporum in until no growth was observed after 9days.